Hipertensão arterial referida e utilização de medicamentos de uso contínuo: um estudo de base populacional - Reginara Alves Ferreira (2012)
INTRODUCTION: Appropriate hypertension treatment is the key to reducing morbidity and mortality related to cardiovascular diseases. However, it is well known that, although individuals with hypertension require antihypertensive drug treatment, a large number does not carry it on. In Brazil, there are no national population-based studies that have investigated the prevalence of the non-utilization of continuous-use medication among individuals who self-reported hypertension. This information is important to target interventions in order to overcome the difficulties of the treatment, especially among the most vulnerable groups. OBJECTIVE: To estimate the prevalence and factors associated with the non-utilization of continuous-use medication among individuals who reported a diagnosis of hypertension in the National Household Sample Survey in 2008 (PNAD 2008). METHODS: We calculated the prevalence of non-utilization of continuous-use medication among 47,268 individuals from 30 to 79 years of age who self-reported having hypertension in the PNAD 2008. The Prevalence ratios with confidence intervals of 95% were obtained by Poisson regression, in order to evaluate the independent association of the sociodemographic characteristics (gender, age, education, residence region, work during the reference week, color / race and per capita household income), health related behaviors (current smoking and regular physical activity) and health characteristics (presence of other chronic diseases, number of physician visits in the 12 past months, hospitalizations reports in the last 12 months and the enrollment in the Family Health Units). RESULTS: The prevalence of hypertensive individuals who do not use continuous-use medication was of 17%. After adjusting, characteristics positively associated with the non-utilization were: males, smokers, living in the North, Northeast and Midwest regions of Brazil and those who were outside the labor force. The non-utilization of continuous-use medication decreased with age, household income, the number of comorbidities and the number of physician visits in the past 12 months. The proportion of non-use was slightly lower among people with higher educational levels (11 and more years of education), those who were outside the labor force and those who did not perform physical activities. CONCLUSION: Although medications for hypertension treatment are available for free in the Brazilian Health System, there are still a considerable proportion of self- reported hypertensive individuals who do not use medication continuously. The control of hypertension is essential in order to face the main non-transmissible chronic diseases. These results reveal that is necessary to invest in primary care, improve access to health services and take action against the regional, social and gender inequalities observed.